2023
DOI: 10.1002/agg2.20347
|View full text |Cite
|
Sign up to set email alerts
|

Cannabidiol industrial hemp growth, biomass, and temporal cannabinoids accumulation under different planting dates in southern Florida

Abstract: Due to limited information, identifying suitable cannabidiol (CBD) dominant industrial hemp (Cannabis sativa L.) cultivars and optimal planting date are critical for hemp commercialization for CBD production in Florida. Two field trials were conducted with seven cultivars planted on three different dates from late April to late June. The cultivars were received from two different suppliers (Kentucky and Colorado) representing their adaptation. Plant growth parameters such as plant height and green canopy cover… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 29 publications
0
5
1
Order By: Relevance
“…Similarly, the effect of planting date was also not consistent among the locations (Figure 4). In other studies with CBD-dominant industrial hemp cultivars, we also found that the effect of location and planting date was not consistent across the cultivars (Chiluwal et al, 2023;Sandhu et al, 2022). We did not see significant location and planting date effect in most of the tested cultivars possibly due to similar environmental conditions during cannabinoid accumulation across all planting dates and locations in the experimental year.…”
Section: Discussioncontrasting
confidence: 65%
See 4 more Smart Citations
“…Similarly, the effect of planting date was also not consistent among the locations (Figure 4). In other studies with CBD-dominant industrial hemp cultivars, we also found that the effect of location and planting date was not consistent across the cultivars (Chiluwal et al, 2023;Sandhu et al, 2022). We did not see significant location and planting date effect in most of the tested cultivars possibly due to similar environmental conditions during cannabinoid accumulation across all planting dates and locations in the experimental year.…”
Section: Discussioncontrasting
confidence: 65%
“…Both THC (<0.1%) and CBD (<0.2%) concentration was very low in both cultivars in this study suggesting there was no or little transformation from CBGA and CBG into THC and CBD in all planting conditions and locations. Hence, the results of this study suggest that CBG‐dominant industrial hemp cultivars could be better suited in Florida's environment as most of the CBD‐dominant cultivars often exceed acceptable THC concentration (Chiluwal et al., 2023; Sandhu et al., 2022; Yang et al., 2020;). However, floral biomass yield was low in both cultivars.…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations